Strategi Komunikasi dalam Mengatasi Konflik Internal di Perguruan Tinggi XYZ (Studi kasus: Antara Departemen Komunikasi Pemasaran dengan Departemen Keuangan) - Dinda Ayu Wardhany; Muhamad Rio Andika (Jurnal Syntax Admiration, 2024)
XYZ College experienced conflict issues at the time of closing new student admissions (PMB) for the 2023-2024 period. This was triggered by the injury time promotion which was carried out during the final seconds of the closing of PMB for the 2023 - 2024 period. This research aims to analyze the communication strategies used in resolving internal conflicts at XYZ High School. Through this research, it is hoped that effective communication strategies can be found to resolve conflicts in this organization. This research can also provide insight and recommendations for XYZ universities and similar organizations in handling conflict effectively. This research uses a qualitative method, a descriptive narrative approach with 2 informants, namely the marketing communications manager and the financial manager of XYZ College. Based on the research results obtained regarding Communication Strategies in Overcoming Internal Conflict at XYZ Higher Education, namely by implementing the three important steps needed to develop a communication strategy according to Anwar Arifin.